Comparing the Performance and Evaluation of Computer Experts and Farmers when Operating Agricultural Robots: A Case of Tangible vs Mouse-Based UIs - Mallas, Andreas; Rigou, Maria; Xenos, Michalis (Human behavior and emerging technologies, 2022)
Tangible user interfaces (TUIs) integrate computer systems with the physical world as they allow interaction through physical objects and the human kinesthetic system. They have been studied in various domains, both by the designing and piloting of innovative applications, as well as by comparatively analyzing TUI against GUI interaction. In the human-robot interaction (HRI) field, TUIs are considered a promising approach as they make effective use of physical object affordances, but research is rather inconclusive about whether TUIs offer improved efficiency, lower error rates, increased intuitiveness, engagement, and user satisfaction. In this study, two prototype UIs were designed and evaluated to compare a TUI with a 2D mouse-based UI for remotely operating two agricultural robots used for vineyard spraying. Two different user groups played the role of the operator: computer experts and farmers leading to an experiment with a 2×2 setup, where two different types of UIs were evaluated by two different user groups. The formulated research questions concern the efficiency, accuracy, and user evaluation for each UI and for each group individually and combined. Analysis has shown that there were no statistically significant differences comparing the alternative UIs for each group in terms of time to complete the task, even though computers experts were faster, as expected. Also, the number of collisions, as well as the percentage of unsprayed and double sprayed area, revealed no significant differences, either for user groups or UIs. The TUI received more positive evaluations in terms of user preference, and users reported lower perceived error rates, especially in the case of farmers, who were also more willing to use the TUI in their daily job.